Sustainability consciousness level among pre-service biology teacher student - Defrian Melta; Lufri Lufri; Fitri Arsih; Sa’diatul Fuadiyah (Assimilation)
The Sustainable Development Goals (SDGs), established by the United Nations in 2015, aim to address global challenges such as poverty, inequality, and climate change. Achieving these goals requires sustainability consciousness, which encompasses awareness, knowledge, attitudes, and behaviour toward sustainable development. This study evaluates the sustainability consciousness of pre-service Biology Education teacher students at Universitas Negeri Padang using the Sustainability Consciousness Questionnaire (SCQ). The SCQ, adapted from Gericke et al. (2018), consists of 50 statements covering economic, social, and environmental dimensions, and assesses sustainability knowingness, attitudes, and behavior using a 4-point Likert scale. Data analysis employed descriptive statistics to categorize respondents into low, medium, and high levels of sustainability consciousness. The results reveal that 88.5% of students demonstrate medium sustainability consciousness, 7.7% exhibit low consciousness, and 3.8% display high consciousness. The study also found that sustainability consciousness was highest in the social dimension, with strong attitudes and behaviors related to social sustainability, while the environmental and economic dimensions showed more variability. These findings underscore the need for targeted educational interventions to enhance sustainability consciousness among pre-service teachers, which is essential for integrating sustainability into higher education curricula.